Age as a Predictor of Burnout in Russian Public Librarians - Kolachev, Nikita; Novikov, Igor (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2020)
Objective – Increasing life expectancy leads to an increase in the mean age of the workforce. The aging workforce implies new challenges for management and human resources. Existing findings on relations between age and burnout are controversial and scarce. Also, the problem of burnout amongst library workers in Russia has received little attention from researchers.Methods – The studied sample consisted of 620 public librarians from 166 public libraries of different regions (the Moscow region, Yaroslavl, Chelyabinsk, Novosibirsk, Astrakhan, and Republic of Buryatia) of the Russian Federation, who completed a self-reported online survey. For measuring burnout, a new Burnout Assessment Tool was implemented. To examine the associations of interest, we used structural equation modeling with a group correction approach. In addition, library location, general self-efficacy, and length of employment at the current workplace were utilized as predictors. All statistical analysis was performed in R.   Results – Findings confirmed the hypotheses partially and revealed negative links between exhaustion, mental distance, and cognitive control and age, while reduced emotional control did not relate to age. Urban librarians tended to demonstrate higher levels of mental distance and had more significant problems with emotional regulation than their rural counterparts. Also, the non-Moscow region librarians did not demonstrate correlations between age and reduced cognitive control. Moreover, they showed a positive link between age and reduced emotional control.  Conclusion – The current paper confirmed some previous results on the negative relations between burnout symptoms and chronological age. The results suggest the existence of higher risks of burnout for younger library workers. Potential mechanisms underlying the resilience of older workers are discussed.